Feasibility Test of Raspberry Pi Based Spectrum Analyzer and Transfer Level Register-Software Defined Radio as Learning Media for Frequency Measurement - Fatmawati Sabur; Mulyadi Nur (STAI Hubbulwathan Duri, 2022)
The purpose of the study was to test the feasibility of a raspberry python-based prototype spectrum analyzer and a software-defined radio-level transfer register designed to meet the practical needs of the Telecommunications Engineering laboratory. For the initial stage, the feasibility test was carried out at SMK Negeri 1 Pangkep, South Sulawesi. The method of data collection was carried out using a test and questionnaire method to determine the effectiveness and feasibility of the developed teaching aids. The subjects for assessing the wireless turn signal system teaching aid were media experts and material experts as many as 2 teaching staff from SMK Negeri 1 Pangkep, Department of Communication and Networking Engineering in the field of wireless Engineering. The results showed that the feasibility of the spectrum analyzer trainer as a learning medium for wireless technology practice based on the results of expert and user tests, it was found that the percentage level of feasibility of wireless learning media as a learning medium was 80.19% which could be categorized as very feasible.